Bioethics and Islamic Values: Assisted Reproductive Technology in the Context of Indonesia - Maizer Said Nahdi; Eka Sulistiyowati (Studia Islamika, 2017)
Assisted-reproductive technology (ART) has developed rapidly, and has brought controversies in terms of legality and ethics. Todays, majority of people rely on bioethics to address the issue. Yet, bioethics in its development, mostly is influenced by Western values such as autonomy, beneficence, non-maleficence, and justice. Some communities, like Islam, need to respond the issue using “Islamic bioethics”. This paper explores how Muslims in Indonesia tackle the issue and set up “Islamic bioethical values” accordingly. Our literary research found that some individual interpretation and judgments (ijtihād) have been given both by Islamic organizations [Muhammadiyah, Nahdlatul Ulama (NU), and Majelis Ulama Indonesia (MUI)] and outstanding ulama. Fatwas issued by the majorities indicate that although the methods of inquiries are different, the result is the same, that is rejecting the presence of a third party in the form of sperm, ovum, or uterus.DOI: 10.15408/sdi.v24i1.2209